2017
DOI: 10.3174/ajnr.a5275
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 30 Spinal Angiograms Falsely Reported as Normal in 18 Patients with Subsequently Documented Spinal Vascular Malformations

Abstract: All the angiograms falsely reported as normal were caused by correctible, operator-dependent factors. The nonrecognition of documented lesions was the most common cause of error. The potential for false-negative studies should be reduced by the adoption of rigorous technical and training standards and by second opinion reviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 8 publications
(9 reference statements)
0
23
0
Order By: Relevance
“…For instance, for the lateral sacral arteries, the catheterization of the internal iliac artery is not sufficient because proximal injection may lead to poor opacification of the lateral sacral arteries (Fig 1). In the article of Barreras et al, 1 most of the missed fistulas (52.9%) were at or below the L4 level, which confirms the need for a complete spinal DSA, including the lower spinal supplies.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…For instance, for the lateral sacral arteries, the catheterization of the internal iliac artery is not sufficient because proximal injection may lead to poor opacification of the lateral sacral arteries (Fig 1). In the article of Barreras et al, 1 most of the missed fistulas (52.9%) were at or below the L4 level, which confirms the need for a complete spinal DSA, including the lower spinal supplies.…”
mentioning
confidence: 77%
“…W e read with great interest the article recently published in the American Journal of Neuroradiology by Barreras et al 1 entitled, "Analysis of 30 Spinal Angiograms Falsely Reported as Normal in 18 Patients with Subsequently Documented Spinal Vascular Malformations." This very valuable article for the interventional neuroradiology and neurosurgical communities presents the causes of false-negative digital subtraction angiography findings for the depiction of spinal dural arteriovenous fistulas (SDAVFs).…”
mentioning
confidence: 99%
“…It occurs when the arteries supplying the nerve roots or dura mater communicate with the spinal drainage vein when passing through the dura mater at the intervertebral foramen. Because the incidence of SDAVF is extremely low and the clinical manifestations are not typical [5], early diagnosis is not easy, and the misdiagnosis rate is high [6,7]. If diagnosis and treatment are delayed, spinal venous pressure continues to increase and can cause spinal cord ischemia and edema and even irreversible injuries, such as necrosis and demyelination.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that recent studies have demonstrated operator-dependent and avoidable missed diagnoses in patients. These factors included: documented but not identified lesions, lack of documenting regions of interest, inadequate injection leading to poor visualization, and involvement of vessels outside of the spine [16].…”
Section: Spinal Digital Subtraction Angiographymentioning
confidence: 99%